PELUANG PENGEMBANGAN AGRIBISNIS SAYUR-SAYURAN DI KABUPATEN KARIMUN, RIAU - Almasdi Syahza (Universitas Riau, 2003)
The objective of tlie .study was to identify the possibility and strategy of vegetables agrobusiness development inKarimun. The Development of vegetables agrobusines.s in Karimun is promising, because of its geographicalcondition. The surrounding areas of Karimun are Batam Island and international trade route: Singapore-Malay,sia-lndonesia. The area is connected to Karimun-Tanjung Pinang lini<age project. The promisingcommodities were: lettuce, petal, celery, legume, bitter mellon, cucumber, mustard greens, leafy vegetable,eggplant Having 500 hectares potential land area use for vegetables, Karimun was expected to be the major ofvegetable supplier for Batam, Tanjung Pinang and Singapore.